INFLUENCE OF CONTENT OF DISCRETE FIBERS IN EPOXY BINDERS ON INDICATORS OF ADHESIVE AND COHESION STRENGTH OF COATINGS - Vorobiov, Pavlo (Scientific Journal "Metallurgy", 2023)
ED-20 epoxy diane binder was used to form epoxy composite materials. Polyethylene polyamine PEPA hardener was used to crosslink the epoxy binder, which allows the materials to be cured at room temperature (q = 10 pts. wt. by weight per 100 pts. wt. by weight of ED-20 epoxy oligomer). To increase the adhesion and cohesion strength, a mixture of discrete fibers with the following parameters was used: l = 15…30 mm, d = 20… 25 μm, containing 52% cotton, 48% polyester. The paper compares the results of the study of adhesion strength at separation, residual stresses and analysis of the fracture surface of the adhesive joint. It is shown that the maximum value of adhesive strength (σа = 42.5 МРа) and minimum residual stresses (σз = 1.5 МРа) are characterized by materials containing a mixture of discrete fibers with a content of q = 0.25 pts. wt. Such films are characterized by cohesive destruction of the surface of the adhesive joint. This is due to the interaction of amide and carbonyl groups of discrete fibers with an epoxy binder. A comprehensive study of physical and mechanical properties, the results of which established the optimal content of a mixture of discrete fibers in the reactoplastic matrix, which is q = 0.50…0.75 pts. wt. per 100 pts. wt. by weight epoxy oligomer ED-20 and 10 pts. wt. firm PEPA. Such composites are characterized by the following properties: toughness – W = 12.7…13.2 kJ/m2; destructive bending stresses – σben = 56.0…62.0 MPa, modulus of elasticity in bending – E = 3.15…3.30 GPa. The increase in mechanical strength indicators is associated with the homogeneity of the polymer structure, where the filler perceives the maximum possible share of stress and redistributes it throughout the volume of the material. Optical microscopy revealed the viscous nature of fracture for composites with the optimal content of fibrous filler, which indicates increased mechanical strength.